2016
DOI: 10.5530/ijper.50.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Chitooligosaccharides Attenuate Lipopolysaccharideinduced Inflammation and Apoptosis of Intestinal Epithelial Cells: Possible Involvement of TLR4/NF-κB Pathway.

Abstract: Marine-derived chitooligosaccharides (CHOS) are a new class of anti-inflammatory natural products characterized by its nontoxity, low-cost and small-molecule. But whether CHOS exert a protective action against inflammatory bowel diseases (IBDs) is not yet fully understood. This paper studied the effect of CHOS on the inflammation and apoptosis of intestinal epithelial cells (IECs) using lipopolysaccharides (LPS)-stimulated Caco-2 cells as an in vitro model of IBD. Caco-2 cells were pre-incubated with various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…In this study, Compelling investigations in humans and other higher organisms have shown that the secretion of pro-inflammatory cytokines can play an essential role in the progression of inflammatory bowel disease (53) . It has been indicated that both CTS and COS supplementation can attenuate intestinal inflammation by suppressing the expression of certain cytokines as well as the production of inflammatory regulators both in vivo (54)(55)(56) and in vitro (57,58) . Hence, according to our present study, it is reasonable that CTS or COS supplementation in fish diet can attenuate SBM-induced inflammatory response in turbot, partially by suppressing the production of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Compelling investigations in humans and other higher organisms have shown that the secretion of pro-inflammatory cytokines can play an essential role in the progression of inflammatory bowel disease (53) . It has been indicated that both CTS and COS supplementation can attenuate intestinal inflammation by suppressing the expression of certain cytokines as well as the production of inflammatory regulators both in vivo (54)(55)(56) and in vitro (57,58) . Hence, according to our present study, it is reasonable that CTS or COS supplementation in fish diet can attenuate SBM-induced inflammatory response in turbot, partially by suppressing the production of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products had received much attention to modulate the immune system since the current treatments induce severe side effects (Mei et al, 2013;Yang et al, 2016). Several natural compounds as polysaccharides and oligosaccharides reported to enhance the immune system (Petrovsky et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is the glycolipid constituent of the outer membrane of all pathogenic gram-negative bacteria that known as one of the most potent activators of the inflammatory responses. LPS activates the inflammatory signal transduction by the cell surface toll-like receptor-4 (TLR-4) that results in cellular activation and pro-inflammatory gene expression (Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it was shown that an oral intake of chitosan oligosaccharide (20 mg/kg/day) alleviated DDS-induced acute and chronic colitis in mice by inhibiting an NF-κB pathway [ 165 ]. Moreover, chitosan oligosaccharide downregulated NF-κB downstream targets such as COX-2 and upstream targets such as TLR-4 in lipopolysaccharide-induced inflammation in intestinal epithelial cells [ 166 ]. Furthermore, 50-200 µg/mL of a highly N -acetylated chitosan oligosaccharide inhibited protein expression of PI3K/Akt signaling pathway, which was involved in proinflammatory cytokine production in RAW 264.7 macrophage cells [ 167 ].…”
Section: Potential Applications Of Chitin and Chitosan Oligosacchamentioning
confidence: 99%